Advancements and Challenges in Active Magnetic Bearings: A Comprehensive Review of Performance, Control, and Future Prospects - Debarghya Dutta (22282726) (2025)
This paper provides an in-depth assessment of Active Magnetic Bearings (AMBs), which are electromagnetic bearings powered by power electronic components for high-speed equipment. The paper highlights the advantages of AMBs as frictionless bearings that utilize magnetic force to support the rotor, resulting in reduced wear, lower losses, and extended lifespan compared to classical ball bearings. AMBs are particularly well-suited for high-speed applications and demonstrate compatibility with both clean environments, such as renewable energy sectors, and challenging conditions like extreme pressures, temperatures, and harsh environments. However, controlling AMBs presents difficulties due to their nonlinear and inherently unstable nature. The paper focuses on examining the benefits and drawbacks of AMBs, including fault analyses. It further emphasizes recent advancements in power electronics supervision, including quick-switching power components, power conversion devices, and advanced control techniques, which have significantly expanded the potential applications of AMBs across various industries. Additionally, the paper explores the electromagnetic setups, electrical converters, sensors, and optimization techniques employed in AMBs, providing valuable insights into their construction, fault-finding methods, control strategies, and ongoing and future research trends. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2024.3523205